Does a Widespread Species Have a Higher Competitive Ability Than an Endemic Species? A Case Study From the Dongting Lake Wetlands - Du, Yuhang; Zhou, Qiaoqiao; Peng, Zenghui; Peng, Fangcheng; Xi, Lianlian; Li, Youzhi (Frontiers in Plant Science, 2022)
The distribution range of plants is usually related to their competitiveness. The competitive ability between common widespread, which are generally considered to be invasive, and common endemic species, is still not very clear. Five plant communities were monitored in the field to compare competitive abilities of widespread species, Phragmites australis, and endemic species, Triarrhena lutarioriparia, in the Dongting Lake wetlands. The ratios of individual numbers of T. lutarioriparia to P. australis per square meter were found to be 9:0, 14:1, 10:5, 7:6, and 0:11 in the five respective communities. A manipulation experiment was then performed with five planting modes (T. lutarioriparia:P. australis was 4:0, 3:1, 2:2, 1:3, and 0:4, respectively). Results from field monitoring showed that the two plant species exhibited similar decreased survival percentages during flooding. P. australis had higher aboveground biomass before the flooding and higher relative elongation rate, whereas T. lutarioriparia had higher aboveground biomass after flooding and a higher relative growth rate. P. australis had a higher competitive ability than T. lutarioriparia before and after the flooding. The manipulation experiment revealed that P. australis had a higher survival percentage than T. lutarioriparia, with no differences in plant biomass, relative growth rate, and the relative elongation rate between the two species. P. australis was found to have a higher competitive ability than T. lutarioriparia in the early growing stage and a lower competitive ability in the middle and later stages. The relative yield total in the field monitoring and manipulation experiment was > 1, indicating that T. lutarioriparia and P. australis occupied different niches in the experimental conditions. It was concluded that, compared with T. lutarioriparia, P. australis has a higher competitive ability in submerged habitat and a lower competitive ability in the non-submerged habitat. The niche differences between the two species enabled their coexistence in the Dongting Lake wetlands with seasonal flooding.